Expedite recovery from esophagectomy and reconstruction for esophageal squamous cell carcinoma after perioperative management protocol reinvention - Liu, Yu-Wei; Yan, Fan-Wei; Tsai, Dong-Lin; Li, Hsien-Pin; Lee, Yen-Lung; Chiang, Hung-Hsing; Hsu, Hung-Te; Chuang, Hung-Yi; Chou, Shah-Hwa (Journal of Thoracic Disease; Vol 9, No 7 (July 31, 2017): Journal of Thoracic Disease, 2017)
Background: Surgery for esophageal cancer is invasive and challenging, and always to be followed with arduous post-operative care and recovery. This study, maybe one of the first in Asian populations, is to determine whether a reinvented protocol for perioperative management for esophageal cancer surgery which is being implemented in our department, will lead to a faster convalescence and also significantly decrease financial burdens garnered by patients during hospitalization. Methods: Operated on by the same surgeon and team in the same hospital, consecutive patients who had received esophagectomy and reconstruction for esophageal squamous cell carcinoma were retrospectively reviewed. On the basis of two different treatment periods, patients were divided into two groups: A and B. Group A was patients who had received the new reinvented protocol between 2012 and 2016, while group B patients were those having received the previous protocol between 2008 and 2011. Their demographics, post-operative outcome, and hospital charges were collected and compared. Results: There were 64 patients in group A, and 69 in group B. Ventilator days (P